Advantages in diagnosis of giant cell arteritis by ultrasound - Wojczal, Joanna; Kozera, Grzegorz; Luchowski, Piotr; Neubauer-Geryk, Jolanta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
Giant cell arteritis is the most common systemic vasculitis. It selectively affects large- and medium-sized arteries. Arterial wall inflammation leads to luminal occlusion and tissue ischemia, which cause the clinical manifestations of this vasculitis. Susceptible sites include the vascular bed of the cranial nerves and scalp including the temporal arteries, optic nerve, masseter muscles, and the posterior circulation of the central nervous system. Involvement can extend to the aorta and its primary and secondary branches, including the subclavian and axillary arteries, which leads to upper-extremity ischemia. The article presents a review of epidemiology, clinical presentation and especially ultrasound diagnostics of giant cell arteritis.